Bilateral inferior alveolar nerve reconstruction with a vascularized sural nerve graft included in a free fibular osteocutaneous flap after segmental mandibulectomy. Issue 5 (23rd December 2015) - Tanaka, Kentaro; Okazaki, Mutsumi; Homma, Tsutomu; Yano, Tomoyuki; Mori, Hiroki
ABSTRACT: Background: Segmental mandibulectomy with bilateral inferior alveolar nerve (IAN) resection results in complete sensory loss in the lower lip and chin. The purpose of this study was for us to report on a bilateral IAN reconstruction with a vascularized nerve graft after chemoradiotherapy during cancer ablation. Methods: The mandible was reconstructed with a fibular osteocutaneous flap that included the sural nerve. The proximal ends of the right and left IAN were sutured to the proximal and distal ends of the sural nerve in an end‐to‐end manner. The 2 distal ends of the mental nerves were sutured to the sural nerve in an end‐to‐side manner. Sensations were measured using the Semmes–Weinstein monofilaments test. Results: Sensory recovery was first noted after 5 months and the quantitative results of the Semmes–Weinstein test 45 months after surgery were 2.83 to 4.08. Conclusion: One‐stage nerve reconstruction may be indicated for bilateral IAN resection. A vascularized nerve graft is effective especially in a perioperative radiotherapy case. © 2015 Wiley Periodicals, Inc. Head Neck 38: E111–E114, 2016